The Effectiveness Of A Task‑Based Program In Developing Arabic Listening Skills For Non‑Native Speakers/ فاعلية برنامج قائم على مدخل المهام في تنمية مهارات الاستماع باللغة العربية للناطقين بغيرها - Abdulrahman Mohsen Hassan; Hassan Shehata (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigated the insufficient Arabic listening skills among Turkish theology faculties (Islamic studies colleges) students, shortcomings in existing Arabic language programs in developing these skills, and the lack of modern teaching approaches and strategies for their enhancement. Consequently, the study aimed to create the Arabic listening skills of non-native-speaking preparatory-year students at these faculties by designing, implementing, and assessing the effectiveness of a task-based instructional program using descriptive and experimental design methods. Employing a one-group pre-test/post-test model with a sample of 30 lower-beginning (A1) level students according to the Common European Framework of Reference for Languages (CEFR). Instrument checklist of Arabic listening skills and an inventory of students' functional listening needs. This inventory was then converted into functional listening tasks, upon which the task-based instructional program was built. A Listening Skills Test was created and administered to the research group before and after the program delivery. The results indicated that the proposed task-based program was highly effective, significantly developing the students' overall listening scores and individual sub-skills. Based on these findings, the study recommends applying the task-based approach in teaching Arabic and developing its listening skills for non-native speakers. Furthermore, it recommends incorporating the proposed task-based program into preparatory-year curricula in theology colleges and providing specialized training for preparatory-year instructors on implementing the task-based approach.